How to safely perform laparoscopic cholecystectomy: anatomical landmarks - S.M. Chooklin; S.S. Chuklin (Медицина неотложных состояний)
Bile duct injury rates in laparoscopic cholecystectomy remain higher than during open cholecystectomy. Intraoperative injuries are mostly the result of a misinterpretation of anatomical structures due to severe inflammation or topographical variations. Standard laparoscopic cholecystectomy requires proper dissection of Calot’s triangle to achieve the critical view of safety (CVS). The CVS is the end product of dissection, and bile duct injuries occur before the conclusion of that process. The CVS cannot always be achieved in cases of severe cholecystitis because of technical difficulties. A complete strategy of safety should therefore include early recognition of difficulties and identification of cholecystectomies, when the CVS cannot be achieved, in order to utilize new intraoperative technologies to clarify the anatomy. Fixed anatomical landmarks can help in proper orientation to ascertain the surgical anatomy correctly during surgery. Encompassed within the review are insights into identifying critical landmarks for assessing the positioning of vital structures in compromised anatomical conditions.